2015
DOI: 10.1128/jvi.01149-15
|View full text |Cite
|
Sign up to set email alerts
|

The ORF61 Protein Encoded by Simian Varicella Virus and Varicella-Zoster Virus Inhibits NF-κB Signaling by Interfering with IκBα Degradation

Abstract: Varicella-zoster virus (VZV) causes chickenpox upon primary infection and establishes latency in ganglia.Reactivation from latency causes herpes zoster, which may be complicated by postherpetic neuralgia. Innate immunity mediated by interferon and proinflammatory cytokines represents the first line of immune defense upon infection and reactivation. VZV is known to interfere with multiple innate immune signaling pathways, including the central transcription factor NF-B. However, the role of these inhibitory mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Recently, it was shown that SVV inhibits type I interferon (IFNa/b) signalling by reducing STAT2 and IRF9 protein levels in infected cells [27]. Furthermore, SVV impaired NFkB signalling by preventing the ubiquitination and degradation of the NFkB inhibitor IkBa [28]. Herein, we have extended these findings by demonstrating that SVV also blocks type II IFN (IFNg) signalling in infected cells.…”
Section: Vaccinia Virus and Hcmv Antagonize Ifng-induced Stat1 Phosphsupporting
confidence: 51%
“…Recently, it was shown that SVV inhibits type I interferon (IFNa/b) signalling by reducing STAT2 and IRF9 protein levels in infected cells [27]. Furthermore, SVV impaired NFkB signalling by preventing the ubiquitination and degradation of the NFkB inhibitor IkBa [28]. Herein, we have extended these findings by demonstrating that SVV also blocks type II IFN (IFNg) signalling in infected cells.…”
Section: Vaccinia Virus and Hcmv Antagonize Ifng-induced Stat1 Phosphsupporting
confidence: 51%
“…Interestingly, immune genes that mapped to antigen presentation were downregulated 3 and 10 DPI, but upregulated 7 DPI. This change in FC direction could be due to initial immune evasion strategies employed by SVV (Whitmer et al, 2015;Meysman et al, 2013) 3 DPI, followed by development of host defense 7 DPI, and again downregulation of these pathways as the immune response begins to resolve 10 DPI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the E3 ubiquitin ligase domain of VZV ORF61 was required to modulate this pathway, downstream of triggering receptors TLR3, TLR8, and TLR9 (87). Use of the SVV model indicated that SVV, like VZV, can prevent ubiquitination of IκBα and additionally prevents the phosphorylation of IκBα (134). This study also revealed that in addition to SVV ORF61, SVV is likely to encode additional modulators of NFκB signaling, as an ORF61 deletion virus retained its capacity to prevent IκBα phosphorylation and degradation.…”
Section: Vzv Modulation Of Mddc Functionmentioning
confidence: 99%